2017
DOI: 10.1680/jsuin.17.00032
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of superhydrophobic zirconium surface with a facile electrodeposition process

Abstract: A superhydrophobic zirconium film with a hierarchical knobbly structure was prepared by a one-step electrochemical method on the surface of steel. Wettability was determined with a water contact angle of 157°and a sliding angle of 3°. The morphology was characterized with scanning electron microscopy, and the microstructure seemed like it is composed of micro-nano complicated particles. Furthermore, according to the results of Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy and energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Researchers have found that many plants and animals have excellent hydrophobicity, such as the surface of lotus leaves and the wings of butterflies. Because its surface has a micro-coarse structure and a low surface energy waxy grain [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that many plants and animals have excellent hydrophobicity, such as the surface of lotus leaves and the wings of butterflies. Because its surface has a micro-coarse structure and a low surface energy waxy grain [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The other category is a one-step electrodeposition method to obtain the surface directly [31,32]. This method is usually performed in an ethanol electrolyte to deposit chemical compounds (usually formed by low surface energy substances and metal cations) onto the cathode surface.…”
Section: Introductionmentioning
confidence: 99%